Effect of pH on Diclofenac–Lysozyme Interaction: Structural and Functional Aspect - Basheeruddin, Mohd; Khan, Sheeza; Ahmed, Neesar; Jamal, Shazia (Frontiers in Molecular Biosciences, 2022)
Under the category of drug (NSAID), diclofenac (DCF) is used in the treatment of a variety of human ailments. It has already been reported that the use of this class of drugs for a longer duration is associated with numerous side effects like cardiovascular implications, reno-medullary complications, etc. In the present study, the effect of DCF on the structure, stability, and function of lysozyme was studied. The study was designed to examine the effect of DCF only at various pH values. Heat-induced denaturation of lysozyme was analyzed in the presence and absence of various molar concentrations of DCF at different pH values. The values of thermodynamic parameters, the midpoint of denaturation (Tm), enthalpy change at Tm (ΔHm), constant pressure heat capacity change (ΔCp), and Gibbs energy change at 25 °C (ΔGDo), thus obtained under a given set of conditions (pH and molar concentration of DCF), demonstrated that (i) DCF destabilized lysozyme in respect of Tm and ΔGDo at all the pH values, (ii) the magnitude of protein destabilization is lesser at acidic pH compared to physiological pH, (iii) structural changes in lysozyme are less projecting at pH 2.0 in contrast to pH 7.0, (iv) quenching is observed at both pH values. Furthermore, the process of protein destabilization in the presence of DCF is entropically driven.